Old soul : a novel - Barker, Susan, 1978- (G. P. Putnam's Sons, 2025)
"In Osaka, two strangers, Jake and Mariko, miss a flight, and over dinner, discover they've both brutally lost loved ones whose paths crossed with the same beguiling woman no one has seen since. Following traces this mysterious person left behind, Jake travels from country to country gathering chilling testimonies from others who encountered her across the decades--a trail of shattered souls that eventually leads him to Theo, a dying sculptor in rural New Mexico, who knows the woman better than anyone--and might just hold the key to who, or what, she is. Part horror, part western, part thriller, Old Soul is a fearlessly bold and genre-defying tale about predation, morality and free will, and one man's quest to bring a centuries-long chain of human devastation to an end." -- Publisher annotation.